THERMAL RADIATION EFFECT ON A BOUYANCY-INDUCED COUETTE FLOW DUE TO NEWTONIAN HEATING IN AN UPSTANDING CHANNEL (FULafia Journal of Science and Technology, 2025)
This paper illustrates the impact of optically thick thermal radiation on buoyancy-induced flow with viscous dissipation and Navier slip condition over an up-facing channel. The modelled equations are nonlinear coupled ordinary differential equations, which are treated with the regular perturbation method. The actions of key parameters controlling the flow behaviour in terms of momentum and energy distributions are demonstrated graphically. The skin friction and Nusselt number on the both surfaces have also been computed. The present study is valid for the limiting case because it is based on comparison with earlier studies that back it up. The significant results from this study are: thermal radiation R act as extra aiding force, ie, growing values of R boosts the fluid temperature and velocity, greater Brickman number represent better convective heating at the channel surface, leading to a stronger temperature and velocity. Additionally, the heat transfer rate weakens as boundary thickness causes less heat transfer gradient. The outcome of this research will contribute significantly in widening the applications of thermal radiation effects for multiple heating devices and industrial uses for energy production in solar systems, wound treatment in medical science, space vehicles and aircraft propulsion in engineering and space technology, to mention a few.
Keywords: Viscous dissipation; Thermal radiation; thermal radiation; Navier slip; thermal buoyancy effect; vertical channel